Attitude towards Online Classes among Nursing Students during COVID-19 Pandemic at Nobel Medical College Teaching Hospital - Adhikari, Sunaina (Journal of Nobel Medical College, 2022)
Background: Corona virus disease pandemic has hastened the adoption of digital technology and online classes have become part of nursing education. The transition from face-to-face learning towards online learning is full of challenges and it is very important to explore students’ viewpoints regarding online classes.Materials and Methods: A descriptive cross-sectional study was carried out at Nobel Medical College among undergraduate nursing students. Non-probability consecutive sampling technique was adopted to collect data and 117 students participated in the study. A self-structured online form was developed and data were collected by a self-administered questionnaire through an online survey method. Data was entered and analyzed by SPSS 22.0 version. A Chi-square test was performed to assess the association between background variables and attitude level.Results: The study revealed that 50.43% of the students had negative attitudes towards online classes. In total, two-thirds (67.5%) of students preferred face-to-face learning. Variables such as age, enrolled nursing program, and year of study was significantly associated (p ≤ 0.05) with students’ attitudes towards online classes.Conclusion: Despite being the alternative solution, almost half of nursing students relatively had negative attitudes towards online classes. Students were more inclined towards face-to-face learning in future days.